Evidence for a DNA Replicative Genome for RNA-Containing Tumor Viruses - Bader, John P. (1970)
The requirement for DNA synthesis in the reproduction of RNA tumor viruses was examined using 5-bromodeoxyuridine (BrdU). Addition of BrdU for the first 12 hr after exposure of cells to Rous sarcoma virus resulted in a large decrease in infectious progeny. However, incorporation of [(3)H]uridine into the viral RNA of virions was unaffected. Also, the numbers of virions visualized by electron microscopy were similar in BrdU-treated and untreated samples. Viral group-specific antigen was synthesized after BrdU treatment, and BrdU had little effect on transformation of cells by Rous sarcoma virus. The results support the hypothesis that the replicative genome of RNA-containing tumor viruses contains DNA.